2013
DOI: 10.1038/sc.2012.165
|View full text |Cite|
|
Sign up to set email alerts
|

Global maps of non-traumatic spinal cord injury epidemiology: towards a living data repository

Abstract: Study design: Literature review. Objectives: Globally map non-traumatic spinal cord injury (NTSCI) incidence, prevalence, survival, level of injury and aetiology. Propose a research framework for NTSCI prevention and launch a repository of NTSCI data. Setting: Initiative of the International Spinal Cord Society Prevention Committee. Methods: Literature search of Medline and Embase (1959-June 2011). Relevant articles in any language regarding adults with NTSCI were included. Stratification of information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(157 citation statements)
references
References 45 publications
3
145
2
Order By: Relevance
“…It is important to emphasize that our results are probably not generalizable to other settings because the occurrence of infections as a cause of SCM globally varies between countries and regions, most notably, and not unexpectedly, between developed and developing countries. 20 Differences between the aetiological pathogens (i.e. bacterial, viral, or parasitic) would be expected to be greatly influenced by geographical and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that our results are probably not generalizable to other settings because the occurrence of infections as a cause of SCM globally varies between countries and regions, most notably, and not unexpectedly, between developed and developing countries. 20 Differences between the aetiological pathogens (i.e. bacterial, viral, or parasitic) would be expected to be greatly influenced by geographical and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…2 Owing to the extensive lifelong consequences for the individual and the economic cost associated with SCI, 1 resulting from both traumatic and nontraumatic aetiologies, research into the rehabilitation outcomes of these patients is essential. The demographic characteristics and rehabilitation outcomes of patients with T-SCI have been extensively studied, 3,4 whereas research into patients with NT-SCI has been noticeably limited until more recently, 5,6 despite some studies suggesting the incidence of NT-SCI to be even greater than that of T-SCI. 3,7 Previous research comparing T-SCI and NT-SCI patients has demonstrated clear differences in demographic characteristics, 8 together with similarities and differences in rehabilitation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This predominance of individuals with paraplegia caused by trauma contrasts with what is indicated by the statistics for both Brazil and other countries. 10,[29][30][31] From the second application, the form of application of the ESES-Brazil differed from that of the Dutch version for some of the participants. In the Dutch study, the ESES was applied personally by the researchers, Table 3 -Reliability test ICC and Bland-Altman (n = 20)…”
Section: Discussionmentioning
confidence: 99%